Implementasi Podcast Sebagai Media Pembelajaran pada Mata Kuliah Media dan Teknologi Pendidikan. - Sofwatillah Amin; Hayumi Hayumi; Nurusshofi Hamalatil Jannah; Itoh Masitoh; Suryani Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
Learning media has an important role in increasing the effectiveness of the teaching and learning process. This study aims to analyze the use of podcasts as a learning medium in the Media and Educational Technology course at the Islamic Religious Education Study Program, Primagraha University. The research approach used is qualitative descriptive, with data collection through observation, interviews, and documentation. The research subjects are students who take the course, selected purposively based on the criteria of active users of social media and digital software. The results of the study show that podcasts are an effective learning medium in increasing students' interest and motivation to learn. Although the majority of students are used to using platforms like YouTube and Instagram, they don't have any experience in producing and distributing podcasts. The implementation of podcasts not only provides a new learning experience, but also encourages creativity and improves students' digital literacy. Group-based learning projects such as Ngajak Podcast show positive responses from students and show increased engagement in exploring educational materials independently. Thus, podcasts can be an alternative learning media that is relevant to technological developments and students' digital habits today.